Transformasi Modal Sosial ke Modal Ekonomi dalam Acara Rasulan di Kalurahan Kemiri Kapanewon Tanjungsari Kabupaten Gunungkidul - Mohamad Firdaus (Jurnal Masyarakat dan Desa, 2021)
This study will discuss and explore the transformation of social capital into economiccapital formed in Kemiri Village, Kapanewon Tanjungsari, Gunungkidul Regency.Rasulan is a form of social capital of the Kemiri community which has been formedsince the ancestors and its existence and sustainability are always maintained. Theform of social capital, which began with the Rasulan event, is the main capital of theKemiri Village community in maintaining the habit of mutual cooperation. Colemanembeds his concept of social capital in the context of rational choice theory. Socialinterdependence arises between actors, as they are attracted to events and resourcescontrolled by other actors to maximize their utility by rationally choosing the bestsolution for them. Furthermore, the maximum utility found in the Kemiri community,one of which is the management of Sogo Lake for Jathilan arts and building rentalsin each hamlet. With the maximum utility as mentioned earlier, it can be understoodthat there was a transformation that was originally present on the organization of theRasulan event as a social model into economic capital that could be utilized by thepeople of Kemiri Village.